The effect of giving sodium butyrate to Holstein calves on gr owth, rumen and blood parameters - Oztas, E; Turkmen, II (Journal of the Hellenic Veterinary Medical Society, 2025)
The aim of this study was to investigate the effects of sodium butyrate supplementation on growth performance, health, rumen, and blood parameters in Holstein calves during the suckling period. Forty-five calves were divided into three groups: one control group and two experimental groups, each consisting of 15 calves matched by birth weight and sex. All groups were provided with 500 grams of milk replacer feed per calf per day and ad libitum access to calf starter feed containing 10% chopped alfalfa hay throughout the experiment. In the Experimental Group I, coated sodium butyrate was added at a concentration of 0.3% to the calf starter feed. In Experimental Group II, 0.3% uncoated sodium butyrate was added to the milk replacer feed, and 0.3% coated sodium butyrate was added to the calf starter feed. The experiment lasted for 60 days. Calves were weighed on the 15th, 30th, 45th, and 60th days of the experiment to assess live weight gain. Sodium butyrate supplementation did not result in significant differences in dry matter intake, daily weight gain, or feed conversion ratio (P > 0.05). However, a significant difference was observed in the glucose levels of blood plasma obtained from samples collected on the 45th day (P = 0.018), while no differences were found on other days. No significant differences were observed in beta-hydroxybutyric acid, blood urea nitrogen, IGF-1, or total serum protein levels. Rumen fluid samples were collected on the 30th and 45th days of the experiment and analyzed for rumen pH and volatile fatty acids. The analyses showed no significant differences between the groups. In conclusion, this study demonstrated that sodium butyrate supplementation in different doses and forms did not significantly affect health or growth parameters in Holstein calves during the suckling period.